AN ANALYSIS OF TEXTUAL FUNCTION ON ENGLISH TEXTBOOK AT SMA WIYATA DHARMA MEDAN - Grace Indryani Pasaribu; Usman Sidabutar; Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the realization of textual function in English listening materials using the Systemic Functional Linguistics (SFL) framework proposed by Halliday. The focus of this study is on the analysis of Theme types, namely Topical, Interpersonal, and Textual Themes, found in clauses 1–85 in Table 4.1. The data were taken from listening texts in an English textbook for Grade XII students. This study employed a qualitative research design using document analysis as the research method. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. Each clause was identified and classified based on its Theme type to examine how textual meaning is organized within the text. Based on the findings, three types of Theme are identified in the data, namely Topical, Interpersonal, and Textual Themes. The results show that Topical Theme is the most dominant type, accounting for (80%) of the total clauses, followed by Interpersonal Theme (10.6%) and Textual Theme (9.4%). Textual Themes are realized through conjunctions, adjuncts, and other linking elements such as if, maybe, and every month, which function to organize and connect ideas within the text. this study demonstrates that textual function plays a significant role in organizing meaning and maintaining coherence in listening texts, particularly through the use of Theme as the point of departure of the message